Surgical resection for local recurrence after radiofrequency ablation for colorectal liver metastasis is more extensive than primary resection. (May 2014) - Kawaguchi, Yoshikuni; Hasegawa, Kiyoshi; Saiura, Akio; Nagata, Rihito; Takahashi, Michiro; Oba, Masaru; Kaneko, Junichi; Aoki, Taku; Sakamoto, Yoshihiro; Sugawara, Yasuhiko; Makuuchi, Masatoshi; Kokudo, Norihiro
Abstract Objective. As a minimally invasive modality, radiofrequency ablation (RFA) has been increasingly applied not only for the treatment of hepatocellular carcinoma, but also for that of colorectal liver metastasis (CLM). However, RFA for CLM has been shown to be associated with a high local recurrence rate, and no optimal treatment for RFA failure has been established yet. The aim of this study was to evaluate the feasibility and outcome of surgical resection for local recurrence after RFA. Material and methods. A retrospective study of 17 patients, who underwent surgery for local recurrence after RFA for resectable CLM, was carried out. The surgical procedures involved in the actual surgery were compared with those envisioned for the primary resection if RFA had not been selected. Results. Surgical resection for RFA recurrence was more invasive than the envisioned surgical procedure in 10 cases (58%). In addition, the proportions of cases that required technically demanding procedures among the patients receiving surgery for RFA recurrence were higher than those in envisioned operations; major hepatectomy, eight cases [47%] versus two cases [12%] (p < 0.0205); excision and/or reconstruction of the major hepatic veins, three cases [18%] versus zero case [0%] (p = 0.035); excision of diaphragm: three cases [18%] versus zero case [0%] (p = 0.035). The 1-, 3- and 5-year overall survival rates were 92%, 45% and 45%, respectively. Conclusions. Surgical resection for RFA recurrence for CLM required more invasive and technically demanding procedures. Thus, RFA for CLM should be limited to unresectable cases, and patients with resectable CLM should be thoroughly advised not to undergo RFA, but rather surgical resection.